PENGEMBANGAN INSTRUMEN EVALUASI PEMBELAJARAN MENGGUNAKAN APLIKASI QUIZIZZ UNTUK MENGUKUR KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK KELAS 5 SDN INPRES PARADOWANE - Muhammad Nilwan; Sri Lastuti; Suriya Ningsyih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research focuses on developing a digital-based learning evaluation tool using the Quizizz platform to assess the critical thinking abilities of fifth-grade students in the IPAS subject